The Intention of Investing Sharia Stocks on Millennials: The Role of Sharia Financial Literacy - Addury, Multazam Mansyur; Nugroho, Anton Priyo; Khalid, Salehuddin (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2020)
Introduction to The Problem: Millennials are a generation that has a very rapid growth. More than 30 percent of Indonesia's population is millennials, but many of the Millennials have not been intentioned in investing in sharia stocks.Purpose/Objective Study: The purpose of this research is to examine the impact of sharia financial literacy on Millennials on the intention of investing in sharia stocks, or it has other factors.Design/Methodology/Approach: This research used Sharia financial literacy and the Theory of Planned Behavior. This research used five variables namely Sharia financial literacy, attitudes, subjective norms, behavioral controls, and intentions. This study used purposive sampling method, from muslim millennials in Yogyakarta. Total respondents to this study are 112 with 20-40 years old or a millennials generation and already have income. Multiple linear regression analysis techniques used as primary analytical techniques.Findings: The results proved that Sharia financial literacy and subjective norms did not affect the intention of investing in sharia stocks. Other variables, such as behavioral attitudes and controls, proved to have a significant influence on the intention of investing in sharia stocks.